Google Gemini as a Learning Assistant: Exploring Student Perceptions - Majidah; Rullyana, Gema; Triandari, Rizki (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
The emergence of Generative Artificial Intelligence (GAI) has had a significant impact on learning. One of the AI ​​technologies that is currently developing is Google Google Gemini, which has excellent potential for use as a learning assistant in physical classrooms. This research aims to understand students' perceptions of using Google Google Gemini as a tool in the learning process, with a focus on four main aspects: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), and Behavioral Intention to Use (BIU). The research method used was a survey involving 45 students of the Educational Technology Study Program, Faculty of Education, Indonesian Universitas Pendidikan Indonesia (UPI). The research results show that students have a very positive perception of Google Google Gemini. In the PU aspect, students feel that Google Google Gemini helps them understand course material, improves learning efficiency, and provides relevant and helpful information during class learning. In the PEOU aspect, students stated that learning to use Google Google Gemini was very easy, interaction with this tool did not require much effort, and the tool had a user-friendly interface. In terms of ATU, students have a very positive attitude towards the use of Google Google Gemini, considering it a good idea and feeling that this tool makes the learning process more enjoyable. Finally, in the BIU aspect, students showed a firm intention to continue using Google Google Gemini in their future academic activities, as well as a desire to recommend this tool to their friends.